Knowledge and perceptions of physiotherapy practitioners towards establishing a geriatric unit in the physiotherapy department at the University Teaching Hospital - Chulu, Malesi (Lusaka: University of Zambia , School of Medicine, 2016)
World population has been experiencing significant ageing, with most of the increase in developing countries. The ageing population in Africa faces a different set of challenges as ageing is highly linked with long term physical and mental disability. These long term chronic conditions are likely to increase personal care needs. There is still absence of geriatric units in physiotherapy departments in Zambia. The main aim of the study was to determine the knowledge and perception of the physiotherapy practitioners towards establishment of geriatric unit in the physiotherapy department, UTH.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Older people--Diseases.; Physical therapy for older people